Impact of a Medical Clinic Relocation on Travel Time: A Tale of 2 Modes of Transportation. (December 2022) - Kahn, Peter A; Ying, Xiaohan; Li, Sunnie; Mathis, Walter S
The aim of this study was to quantify access disparities by examining the impact of a medical clinic relocation on travel time differences for patients using private cars versus public transit. Longitude and latitude of patient home addresses were extracted from electronic medical records for the 4 years before the clinic move. Using offline, open-source, and HIPAA-compliant routing software, roundtrip travel times were computed from each home address to the old and new clinic locations via car and bus. Mean roundtrip travel time by a car changed from 41.3 (IQR 16.1-80.7) to 45.4 (IQR 25.9-78.1) minutes, a 9.9% increase. Mean roundtrip travel time by public transit changed from 67.5 (IQR 51.5-100.2) to 120.8 (100.3-156.1) minutes, a 78.9% increase. Even clinic relocations that minimally impact car travel times can nevertheless yield substantial changes to those traveling by public transit. Clinics and health systems that wish to reduce barriers to accessing health care, especially among those already facing structural inequities, would benefit from utilizing the analytic approach described here.